Workplace culture emotional intelligence and trust in the prediction of workplace outcomes - Luke A. Downey; Jason Roberts; Con Stough (International Journal of Business Science & Applied Management (IJBSAM), 2011)
There were two aims of this study. The first was to assess the reliability of a new measure of emotional intelligence (EI), the Workplace Culture version of the Swinburne University Emotional Intelligence Test (SUEIT) which was designed to measure EI at a group level. The second aim of the study was to investigate the pre-conditions required for the formation of an emotionally intelligent group culture. Specifically, the study proposed that team leader trustworthiness at the leader/member dyad level was required for the formation of an emotionally intelligent culture at the group level. The sample comprised of 142 participants, of which 54 were male and 88 were female. Participants completed a questionnaire assessing perceptions of group EI, leader trustworthiness, job satisfaction and organizational commitment. Results of the study showed that the Workplace Culture SUEIT was reliable and predicted job satisfaction and organizational commitment. Furthermore, trustworthiness of the team leader was found to be significantly correlated to dimensions of group level EI, job satisfaction and organizational commitment. It was concluded that the Workplace Culture SUEIT is a valid and useful tool for measuring group level EI. Furthermore, it was concluded that there is a significant relationship between group level EI and leader/member trust. Implications of the results and future research concerning group and leader EI are discussed.
Keywords: 650; Emotional Intelligence; Culture; Job Satisfaction; Organizational Commitment